Evaluación de una propuesta de un sistema de tratamiento para el agua residual industrial generada en una empresa de saborizantes (2019)
In this project, a proposal is made for a treatment system for wastewater from the production process of artificial flavorings; For this purpose, the industrial wastewater was diagnosed, where the critical parameters were determined that do not comply with the resolution 631 of 2015 that controls the discharges to the water bodies. With the diagnosis of the physical and chemical properties, we proceeded to evaluate the treatment system proposed experimentally by means of laboratory simulation of the equipment required for the development of the treatment system, determining the operating conditions, the necessary reagents and their respective dosages for achieve the greatest removal of contaminants. Finally, the design of the treatment system was made by sizing the equipment and dosing the chemical reagents, to finally analyze the costs of investment, operation and characterization of the wastewater of the proposed alternative.